Inefficiency of Social Assistance in Reducing Poverty Rates: Recommendations for Alternative Social Policies for Poverty Alleviation in Indonesia. - Wimmy Haliim; Ja'far Muhammad (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2025)
This article discusses the dominance of social assistance (bantuan sosial/bansos) policies in poverty alleviation in Indonesia, focusing on the political, social, and economic dynamics that influence their implementation. It is emphasized that social assistance, such as the Family Hope Program (Program Keluarga Harapan/PKH) and Direct Cash Assistance (Bantuan Langsung Tunai/BLT), are often the main instruments for short-term poverty reduction, especially in crises. However, their use is frequently politicized, especially in the run-up to elections, as a tool to strengthen the political legitimacy of those in power. This study also critiques the effectiveness of social assistance in addressing the root causes of poverty, such as access to education, employment, and structural reform. The paradox of increasing the allocation of the social assistance budget compared to the rate of poverty reduction suggests that this approach is less significant in the long term. This article proposes alternative policies, including Universal Basic Income (UBI), local economic empowerment, vocational training, and technology-based distribution reforms to increase transparency. The GEAR (Growth, Empowerment, Adaptive, Rational) social policy model is proposed as a strategic framework to reduce community dependence on social assistance, optimize resource distribution, and ensure the sustainability of socio-economic development.